Two-Tier Diagnostics for Evaluating Submicroscopic Representations in Stoichiometry - Muhammad Fath Azzajjad; Dewi Satria Ahmar; Ahmad Kadir Kilo (Jambura Journal of Educational Chemistry, 2026)
Stoichiometry is a fundamental concept in chemistry that requires students to coordinate symbolic calculations with submicroscopic representations of particles and reactions. However, previous studies consistently show that students often rely on algorithmic procedures without developing coherent particle-level reasoning, leading to persistent misconceptions. This representational gap remains a major challenge in Basic Chemistry instruction. Therefore, this study aimed to examine the effectiveness of audiovisual-supported Problem-Based Learning (PBL) in enhancing students’ submicroscopic representational ability in stoichiometry using a two-tier diagnostic approach. A quasi-experimental design with a posttest-only comparison was employed involving 33 undergraduate students enrolled in a Basic Chemistry course. Participants were divided into two groups with equivalent initial ability distributions: an experimental group receiving PBL integrated with audiovisual media (n = 16) and a control group receiving PBL without audiovisual support (n = 17). Students’ submicroscopic understanding was measured using a two-tier multiple-choice diagnostic test assessing both response accuracy and particle-level reasoning. Data were analyzed through descriptive statistics, diagnostic category profiling, and effect size estimation. The results reveal that the experimental group demonstrated substantially higher levels of coherent submicroscopic representation and significantly lower misconception rates than the control group. Learning gains were consistent across all stoichiometry subtopics, with particularly strong effects observed in relational and inferential tasks such as particle ratio interpretation and limiting-reactant reasoning (Cohen’s d = 1.41). These findings indicate that audiovisual-supported PBL effectively facilitates students’ transition from procedural problem solving to meaningful particle-level understanding. The study underscores the importance of integrating representationally rich instructional media and diagnostic assessments to promote deeper conceptual learning in stoichiometry and chemistry education.